XII Century Natural Philosophy in the Islamic World - Beas Portillo, Carlos (2006)
In  the  first part of  this essay, we will develop an  idea of the Islamic science, which makes it possible to understand its integration in the field of Metaphysics. In the second part, we will develop some key notions in ibn Sina's Natural Philosophy, which shows how the human reality is linked to the scientific conception of nature, and completely inserted in it, as opposed to what occurs in the Modern Scientific Paradigm.